2013
DOI: 10.1007/s13204-013-0249-2
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical model for the peristaltic flow of nanofluid through eccentric tubes comprising porous medium

Abstract: Mathematical model for peristaltic flow of nanofluid between eccentric tubes is investigated through a porous medium. Assumptions of long wavelength and low Reynolds number are carried out to observe the intestinal flow. The flow is considered to be unsteady and incompressible. Analytical solutions are evaluated through homotopy perturbation method. The expression of pressure rise is obtained through numerical integration whose data is presented in table. The problems under consideration are made dimensionless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…More applications of nanoparticles can be seen through Refs. Sheikholeslami et al (2012), Kuznetsov and Nield (2010), Vajravelu et al (2011), Hamad and Ferdows (2012a, b), Akbar and Nadeem (2011, Akbar 2013, , , Nadeem et al (2014), Ellahi et al (2014), Nadeem et al (2014).…”
Section: Introductionmentioning
confidence: 99%
“…More applications of nanoparticles can be seen through Refs. Sheikholeslami et al (2012), Kuznetsov and Nield (2010), Vajravelu et al (2011), Hamad and Ferdows (2012a, b), Akbar and Nadeem (2011, Akbar 2013, , , Nadeem et al (2014), Ellahi et al (2014), Nadeem et al (2014).…”
Section: Introductionmentioning
confidence: 99%
“…A large amount of literature is available which deals with the study of nanofluid and its applications. Nadeem et al [1] have discussed mathematical model for the peristaltic flow of nanofluid through eccentric tubes comprising porous medium. Eldabe et al [2] have investigated the peristaltic transport of manetohydrodynamic Carreau nanofluid with heat and mass transfer inside asymmetric channel.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Nadeem et al . 15 used the homotopy perturbation technique to investigate the peristalsis of an incompressible nanofluid in the porous region of a vertical annulus; equations were derived and solved with a low Reynolds number and long wavelength approximation. The researchers concluded that the peristaltic pumping rate increases as the local NP Grashof number is increased.…”
Section: Introductionmentioning
confidence: 99%
“…Often, the heating effect in metallic NPs is amplified in the presence of electromagnetic radiation 19 . Moreover, the combination of magnetic fields with peristaltic flows has significant applications in biomedical engineering problems 11,1518,20,23–28 . Abdelsalam and Vafai 29 investigated the magnetohydrodynamic peristaltic flow of a non-Newtonian fluid in the porous space of a microchannel.…”
Section: Introductionmentioning
confidence: 99%